ROLE OF ALGAE AND SEAWEED EXTRACT AS BIO-FERTILIZER IN IMPROVING GROWTH, YIELD, AND YIELD COMPONENTS OF ROSELLE (Hibiscus sabdariffa L.) - Rabar Salih (Science Journal of University of Zakho, 2025)
Universal climate change causes to think about applying bio-fertilizers as an alternative way of using synthetic fertilizers, since more uses of artificial fertilizers are contaminating the soil, water, and air, and also it is the major contributor to raise greenhouse gas (GHG) emissions and lastly, harming the earth. During this current study, green algae and seaweed were used as a bio-fertilizer to provide soil nutrients resulting in higher roselle (Hibiscus sabdariffa L.) crop productivity. Different levels of algae (0.0, 0.5 and 1.0 t ha-1) and also seaweed (0.0 and 0.5 t ha-1), were applied to the soil. Seeds of roselle were sowed in the summer season of 2024. Results presented that applying 0.5 t ha-1 of algae was superior on other levels and also on seaweed for most of the growth and yield parameters of roselle plant, such as stem diameter, number of branches per plant, number of fruits per plant, and calyx dry weight (23.3mm, 9.7, 84.3, and 20.0 g plant-1), respectively. While, the longest fruit length was recorded for algae at the level of 1.0 t ha-1 by (31.5mm). Generally, green algae were better than seaweed for all productivity characteristics. This makes us pay more attention to protect the environment and sustainable agriculture through applying algae